Prediksi Kebangkrutan dengan Altman Z-Score dan Springate pada Maskapai Penerbangan Terdaftar di BEI Periode 2016-2023 - Gita Mustika; Ratnawaty Marginingsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
An airline is a company that offers air transportation services for passengers and cargo. This research aims to analyze bankruptcy predictions for airline companies listed on the Indonesia Stock Exchange (BEI) during the 2016-2023 period using the Altman Z-Score (Modified) model and the Springate model. The research population consists of 12 companies operating in the transportation subsector, focusing on the air transportation industry (airlines). The sample used includes 2 airline companies listed on the IDX, namely PT Garuda Indonesia (Persero) Tbk (GIAA) and PT Jaya Trishindo Tbk (HELI). The data collection technique involves documentation in the form of secondary data, specifically the financial reports of airline companies available on the IDX or each company's website. The results of the study show that PT Garuda Indonesia (Persero) Tbk demonstrates potential bankruptcy according to the Modified Altman Z-Score with an average Z-Score of 0.568. However, this company is considered healthy by Springate with an average S-Score of 0,913. Meanwhile, PT Jaya Trishindo Tbk (HELI) is in a grey area according to the Modified Altman Z-Score with an average Z-Score of 1,101, but shows potential bankruptcy according to Springate with an average S-Score of 0,806.